New Creative Educational Technologies for Inter-university Network. (2015) - Pryanichnikov, V.E.; Katalinic, B.; Kirilchenko, A.A.; Khelemendik, R.V.; Kuvshinov, S.V.; Vician, D.; Uglesic, A.
Abstract: We describe new educational technology (project "Intelligent Robotronics") designed as a spatially distributed virtual network for the remote training of engineers, humanitarians, marine specialists, and IT-professionals (all courses involve real mechatronic devices). Mobile robots and mechatronic devices in different cities and universities are incorporated into the virtual network laboratory on the basis of VPN-tunnels through the Internet by special network software. This software was designed for supervising control of robotic systems and remote dynamic reprogramming for all elements in the network from any location. It serves as a basis for robotics software R&D of different manufacturers (AMUR, Robotino, etc.) and may be used for SLAM tasks and supervision control for mechatronic devices via channels with unpredictable delays. The considered problem is how to create the intelligent level of the software, find an adequate knowledge representations and evidences for mobile robots, based on mathematical logic, and suggested IGEC technology.